KARAKTERISTIK OSEANOGRAFI UNTUK MENDUKUNG AGROEKOSISTEM DI KUTAI TIMUR PROVINSI KALIMANTAN TIMUR - Dewi, Ira Puspita (Torani Journal of Fisheries and Marine Science, 2014)
This study aims to determine the character of the waves, bathymetry, currents and tidal in 2012 in East Kutai.Significant wave height derived from AVISO, satellite altimeter TOPEX/POSEIDON, Jason 1 and Jason 2.Water depth data obtained from the C-MAP Norway map with a scale of 1: 250,000. Monthly surface currentdata obtained from JODC. Ebb tidal predictions obtained from DISHIDROS Navy. Wave data processingmethod using the ODV and processed with Surfer 8. Bathymetry visualized in 3D and 2D using Surfer 8 andArcGIS 10. Distribution of surface currents visualized with Surfer 8 wherein the interpolation process previouslyperformed on each cell domain area and conducted breakline on the cell data is mainland. Results showed thatthe wave pattern follows the seasonal wind patterns. Waves in the sea around the waters off of East Kutai have aheight ranging from 0.45 - 0.66 meters. High waves occur in the east of the season (July - August) wheregeographically these waters open to the east. The depth of the water reaches > 100 m at a distance of 3 milesfrom the coast, where the exposure to a wider shallow coastal can be seen around the mouth of the GulfSangkulirang. Current velocity relatively strong in March flows ranged from 0.13 - 1.75 m/sec with an averageof 1.32 m/sec. Generally move in the direction of flow from north to south following the pattern-orientedmorphology North Makassar Straits - south. Type tides are "mixed tide prevailing semidiurnal", where in oneday occurred twice ups and downs twice with different heights and periods. Keywords: wave, bathymetry, currents, tidal